Aldomà, Ignasi (2009): Atles de la nova ruralitat - Cuadrado Ciuraneta, Sergi (Documents d'Anàlisi Geogràfica, 2011)
Aldomà, Ignasi (2009) Atles de la nova ruralitat Fundació del Món Rural, 264 p. ISBN: 978-84-613-2287-9